The low-temperature preparation for crystalline Sb2S3 thin films and photovoltaic performance of the corresponding solar cells. (15th March 2021) - Yang, Yang; Shi, Chengwu; Lv, Kai; Wang, Qi; Guo, Fuling; Chen, Wangchao
Graphical abstract: Highlights: Crystalline Sb2 S3 thin films at the pyrolysis-crystallization temperature of 200 °C. The influence of ethanol and DMF on the morphology of the Sb2 S3 thin films. The Sb2 S3 thin films with the preferential orientation of (0 2 0) were obtained. The PCE of the solar cells achieved 5% for ethanol and 5.44% for DMF. Abstract: The crystalline Sb2 S3 thin films with the preferential orientation of (0 2 0) were firstly prepared at the low pyrolysis-crystallization temperature of 200 °C using the mixture solution of Sb2 O3, CS2, n -butylamine in ethanol or DMF as solvents. The influence of solvent ethanol and DMF on the morphology of the Sb2 S3 thin films was compared and photovoltaic performance of the corresponding solar cells was evaluated. The power conversion efficiency of the Sb2 S3 thin film solar cells achieved 5.00% for ethanol and 5.44% for DMF.